(untitled) (Fiep Bulletin - online, 2013)
The objective of this research was to describe the prevalence of overweight and obesity, as well to realize a comparison of values encountered in ages from 12 to 14 years and the gender in school teenagers. Regarding the methods, the obesity was calculated through the Body Mass Index based on cutoff, adjusted to the age and sex. To verify the behavior of the samples studied in relation to prevalence of overweight and obesity, we recurred to observed percentages. We used the X² to determine the differences between genders and ages, relatively to incidence of obesity. The results revealed that prevalence of overweight was 9%; the girls presented a higher prevalence (10.7%) in relation to the boys (7.3%); the overweight rate occurred of growing kind according ages (9% to the 12 years, 10% to the 13 years and 11% to the 14 years); were found higher indexes of overweight from 13 to 14 years for girls (12%). In case of boys, the 12 years old group was that presented the highest values (10%). We conclude the results encountered showed that prevalence of overweight in Montes Claros city presents preoccupant values requesting preventative measures.